LEARNING MANAGEMENT IN THE DEVELOPMENT FINE MOTOR ASPECT AND CHILDREN’S INDEPENDENCE - Purwanti, Ratna; Rizkieya, Rizkieya; Mujiyat, Mujiyat (E-CHIEF Journal, 2024)
The problem in this research is the results of the fine motor development of children in group A2. This research approach uses qualitative with the type of classroom action research, carried out in 4 meetings, research setting on 12 children in group A2. Data collection techniques use observation, documentation and interviews. Data analysis was carried out using qualitative descriptive techniques which were explained using cross tabulations and graphs which were presented with established indicators of development success. This research aims to describe teacher activities, as well as analyze children's activity, independence and fine motoric aspects. The results of this research show that the teacher's activities reach the very good category, the children's activities reach the very active category, the children's independence reaches the very independent category, and the children's fine motoric aspects reach the very well developed category. It is recommended that school principals, teachers and researchers can then provide input for information to improve children's learning.